The concept of structural information and possible applications - Bielecki, Andrzej; Stocki, Ryszard (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
In this paper, the concept of structural information is presented. The mathematical foundation of the concept is put forward, and the nature of information encoded in a structure is studied. A method for calculating the amount of structural information is introduced. An application to the analysis of cognitive maps is also presented and discussed.